Comparative Analysis of Modified Laparoscopic Swenson and Laparoscopic Soave Procedure for Short-Segment Hirschsprung Disease in Children - Deng, Xiaogeng; Wu, Yaohao; Zeng, LeXiang; Zhang, Jie; Zhou, Jiajia; Qiu, Ronglin (European Journal of Pediatric Surgery, 2015)
Introduction This clinical analysis compared the characteristics and outcomes of modified laparoscopic Swenson (MLSw) and laparoscopic Soave (LS) procedures for short-segment Hirschsprung disease (HD) in children.Patients and Methods This clinical analysis involved a retrospective series of 42 pediatric patients with HD who underwent surgery from March 2007 to July 2012. Patients were divided into two groups: the LS group (n = 15) and the MLSw group (n = 27). Preoperative, operative, and postoperative data were collected, through patient follow-up periods ranging from 12 to 48 months, to compare perioperative/operative characteristics, postoperative complications, and outcomes between the two groups. Major measurements were analyzed statistically.Results On average, the patients in the LS group had a longer operating time (mean ± standard deviation, 199 ± 60 minutes) than those in the MLSw group (148 ± 23 minutes) (p < 0.05). Blood loss was significantly less in the MLSw group (10 ± 7 mL) than in the LS group (26 ± 14 mL) (p < 0.05). There was no difference in feeding time between the two groups (p > 0.05). The MLSw group was discharged after a shorter hospitalization time (8 ± 2 days) than the LS group (12 ± 4 days) (p < 0.05). The MLSw group had lower incidences of soiling (5, 18.5% vs. 7, 46.7%) and constipation (1, 3.7% vs. 3, 20%) than the LS group in the early postoperative period, but no difference was found between the two groups in the rate of complications during the late postoperative period.Conclusions The MLSw procedure did not increase the risk of injury to vital intrapelvic structures or the incidence of complications in surgery for short-segment HD. The early postoperative outcome was much better in the MLSw group than in the LS group, but long-term outcomes were similar. However, the MLSw procedure was simpler, resulting in reduced operating time and less intraoperative blood loss.
Keywords: laparoscopic; Swenson; Soave; pediatric; Hirschsprung disease